1992
DOI: 10.5980/jpnjurol1989.83.1094
|View full text |Cite
|
Sign up to set email alerts
|

Vesical Ultrasonography and Internal Examination of Female Patients With Urethral Syndrome

Abstract: Transabdominal ultrasonography of the bladder and internal examination were performed in 80 female patients without pyuria. They were divided into 3 groups: urethral syndrome with trigonitis (49 cases), asymptomatic trigonitis (16 cases) and normal bladder (15 cases) by cystoscopy. Ultrasonography of trigonitis with or without symptoms showed focal dilation of the submucosal low echo zone and mucosal irregularity around the bladder neck. On the sagittal view, the thicknesses from the surface of mucosa to that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2003
2003
2003
2003

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Local thickening of the mucosa was reported to persist for a long period, even after drug therapy (Chinese herbal medicines, such as, chorei‐to or chorei‐to‐go‐shimotsu‐to) controlled lower urinary tract symptoms 15 . Clinically, there is tenderness of the anterior vaginal wall near the bladder neck in patients with the urethral syndrome, while this is rare in patients with asymptomatic trigonitis 9 . Therefore, local thickening of the vesical mucosa means that inflammation has occurred around this site at some time, but does not necessarily reflect the current severity of inflammation or lower urinary tract symptoms.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…Local thickening of the mucosa was reported to persist for a long period, even after drug therapy (Chinese herbal medicines, such as, chorei‐to or chorei‐to‐go‐shimotsu‐to) controlled lower urinary tract symptoms 15 . Clinically, there is tenderness of the anterior vaginal wall near the bladder neck in patients with the urethral syndrome, while this is rare in patients with asymptomatic trigonitis 9 . Therefore, local thickening of the vesical mucosa means that inflammation has occurred around this site at some time, but does not necessarily reflect the current severity of inflammation or lower urinary tract symptoms.…”
Section: Discussionmentioning
confidence: 91%
“…The present study confirmed our previous finding that the vesical mucosal thickness did not differ between patients with asymptomatic trigonitis and patients with the urethral syndrome. 9 Local thickening of the mucosa was reported to persist for a long period, even after drug therapy (Chinese herbal medicines, such as, chorei-to or chorei-to-go-shimotsu-to) controlled lower urinary tract symptoms. 15 Clinically, there is tenderness of the anterior vaginal wall near the bladder neck in patients with the urethral syndrome, while this is rare in patients with asymptomatic trigonitis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations